2010
DOI: 10.3109/09513591003632134
|View full text |Cite
|
Sign up to set email alerts
|

Antimullerian hormone levels after laparoscopic endometrioma stripping surgery

Abstract: The presence of the endometrioma does not impair the AMH levels. Laparoscopic endometrioma stripping surgery do not appear to cause a damage in the AMH secreting healthy ovarian tissue, in the short-term follow-up. Laparoscopic stripping surgery of endometriomas in experienced hands is currently a valid approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 16 publications
2
52
0
3
Order By: Relevance
“…Not all studies found decreased serum AMH level after laparoscopic endometrioma excision. For example, Ercan et al (22) measured serum AMH levels in 47 patients with endometrioma (33 unilateral and 14 bilateral) 1 month after surgery. In this short-term follow-up they did not observe a significant reduction in the mean serum AMH level postoperatively (1.62-1.39 ng/mL; P>.05).…”
Section: Serum Amh Level (Ng/ml)mentioning
confidence: 98%
“…Not all studies found decreased serum AMH level after laparoscopic endometrioma excision. For example, Ercan et al (22) measured serum AMH levels in 47 patients with endometrioma (33 unilateral and 14 bilateral) 1 month after surgery. In this short-term follow-up they did not observe a significant reduction in the mean serum AMH level postoperatively (1.62-1.39 ng/mL; P>.05).…”
Section: Serum Amh Level (Ng/ml)mentioning
confidence: 98%
“…One recent report found an insignificant association between post-surgical serum AMH levels and size of endometrioma (12) and another study demonstrated variable time-dependent changes in serum AMH levels after ovarian surgery (13). However, information regarding association between post-cystectomy serum AMH levels and presence of normal ovarian tissue containing follicles within cyst wall is lacking.…”
mentioning
confidence: 94%
“…They found largest decline in serum AMH levels one week after surgery and variable recovery during follow-up periods. Indeed, complete recovery of serum AMH levels was not observed at three month after surgery F&S 10295 decline and resubmit 12 especially in women with endometrioma (12). Women with endometrioma may need longer duration for recovery in serum AMH levels, because surgical injury itself and inflammatory reaction could be more detrimental to the surrounding ovarian cortex in these women.…”
mentioning
confidence: 99%
“…This is consistent with other studies with follow-up periods of one month. 10 One month after surgery a significant decline in serum AMH levels were detected by Hirokawa et al 11 and Iwase et al 12 but not by Ercan et al 13 and Litta et al 14 Increased age as the independent risk factor for decreasing the ovarian reserve, could be responsible for decreased levels of AMH one month postoperatively. Jaduol and co-workers 15 performed a review to determine the effects of age on AMH.…”
Section: Discussionmentioning
confidence: 94%